2017
DOI: 10.1590/0037-8682-0116-2017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for intestinal parasite infections in pediatric patients admitted to public hospitals in Southern Brazil

Abstract: Introduction: This study aimed to evaluate the prevalence of intestinal parasitosis and to identify risk factors associated therewith in hospitalized children. Methods: Three fecal samples from each patient were evaluated using three different techniques. The patients' nutritional and socioeconomic status and hematologic profi les were evaluated. Results: Of 106 children, 32.1% tested positive for intestinal parasitosis. The associated risk factors were low parental education levels and children's nail-biting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
2
5
0
3
Order By: Relevance
“…We observed that G. lamblia infection was more common in older children. This finding was also observed in other studies; -in hospitalized children from Manhiça district in the south region of Mozambique, Brazil and Cuba [5,7,36,37]. Children's habits can explain this finding.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 86%
See 1 more Smart Citation
“…We observed that G. lamblia infection was more common in older children. This finding was also observed in other studies; -in hospitalized children from Manhiça district in the south region of Mozambique, Brazil and Cuba [5,7,36,37]. Children's habits can explain this finding.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 86%
“…Having a developing immune system, being undernourished, and animal contact are risk factors for intestinal parasite infection [2,7,8]. Symptoms of intestinal parasites can include lack of appetite, anemia, abdominal pains, cognitive impairment, fever, vomiting, malabsorption, and diarrhea [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This type of infections may also be used as socioeconomic development indicators. Nevertheless, current data on intestinal infections concerning hospitalized children anywhere is still limited [6,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we were able to identify age as a risk factor for global intestinal parasitic infection. It is widely known that older children are more exposed to greater transmission risk due to the inadequate personal hygiene habits and greater contact with the soil than younger children [26,36,37,40]. It is believed that children harbour higher levels of intestinal pathogens and eggs of helminths, thereby exposure to their feces poses a greater risk to health [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…It addressed the main intestinal parasitoses that are found in the region and measures that should be taken to avoid them. The booklet had illustrations and information on parasites which had been diagnosed by the latest studies that were carried out in the region (Almeida et al, 2017;Jeske et al, 2018).…”
Section: Educational Materialsmentioning
confidence: 99%